Prevalence of colonic diverticulosis in ulcerative colitis [Ülseratif kolitte divertikülozis prevalansi] - (:unkn) unknown (My University, 2009)
Background and Objective: Colonic divcrticulosis is characterized by abnormal thickening of the large bowel wall, excess luminal pressure and an increase in sigmoid contractility. The anatomic features intrinsic to the colon, alterations in the colonic wall with aging, motor dysfunction and increased intraluminal pressure, may all play role in the development of divcrticulosis. In ulcerative colitis (UC) chronic inflammatory activity causes reduction in bowel wall muscle tone and contractility. Patients with L'C often have liquid stools and low intracolonic pressure. The objective of this study was an evaluation of the frequency of colonic divcrticulosis in patients with UC and a comparison with that of a control group. Material and Method: Colonoscopic findings of 100 patients older than 50 years with ulcerative colitis were retrospectively evaluated for the presence of divcrticulosis and compared with those of 100 patients who underwent colonic cancer screening colonoscopy. Results: Colonic divcrticulosis was present in only 1 of 100 patients with UC (1%) and in 28 of 100 patients (28%) without ulcerative colitis (p <0.0001). Conclusion: Patients over 50 years of age with UC show a significantly lower frequency of colonic divcrticulosis, suggesting that the motor changes produced by chronic bowel wall inflammation of UC may prevent divertuculosis.
Keywords: Colonic diverticulosis; Ulcerative colitis